Therapeutic effects and long-term outcomes of HMGB1-targeted therapy in rats and mice with traumatic spinal cord injury: A systematic review and meta-analysis - Deng, Chen; Deng, Li; Lv, Junqiao; Sun, Lin (Frontiers in Neuroscience, 2022)
Background To date, the clinical need for therapeutic methods to prevent traumatic spinal cord injury (TSCI) progression and improve functional recovery has not been met. High mobility group box-1 (HMGB1) is released by necrotic neurons or secreted by glial cells after TSCI and plays an important role in pathophysiology. Objective The purpose of this study was to evaluate the effects of HMGB1-targeted therapy on locomotor function recovery, inflammation reduction, edema attenuation, and apoptosis reduction in rat and mouse models of TSCI. Methods We reviewed the literature on HMGB1-targeted therapy in the treatment and prognosis of TSCI. Twelve articles were identified and analyzed from four online databases (PubMed, Web of Science, Cochrane Library and Embase) based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and strict inclusion criteria. Results The methodological quality of the 12 articles was poor. The results of the meta-analysis showed that compared with the SCI group, the treatment group had significantly increased locomotor function scores after SCI [n = 159, standardized mean difference (SMD) = 2.31, 95% confidence interval (CI) (1.52, 3.10), P < 0.00001], and the change in locomotor function scores was significantly increased in both the drug and anti-HMGB1 Ab groups (P < 0.000001 and P < 0.000001). A subgroup analysis showed significant differences (P > 0.05) between the drug group [(SMD) = 1.95, 95% CI (0.95, 2.94), P = 0.0001] and the anti-HMGB1 Ab group [(SMD) = 2.89, 95% CI (1.66, 4.13), P < 0.00001]. Compared with the SCI group, HMGB1 expression was significantly diminished [n = 76, SMD = −2.31, 95% CI (−3.71, −0.91), P = 0.001], TNF-α levels were significantly reduced [n = 76, SMD = −2.52, 95% CI (−3.77, −1.27), P < 0.0001], water content was significantly reduced [n = 44, SMD = −3.94, 95% CI (−6.28, −1.61), P = 0.0009], and the number of apoptotic cells was significantly diminished [n = 36, SMD = −3.31, 95% CI (−6.40, −0.22), P = 0.04] in the spinal cord of the treatment group. Conclusion HMGB1-targeted therapy improves locomotor function, reduces inflammation, attenuates edema, and reduces apoptosis in rats and mice with TSCI. Intrathecal injection of anti-HMGB1 Ab 0-3 h after SCI may be the most efficacious treatment. Systematic review registration PROSPERO, identifier: CRD42022326114.